Witnessing hateful people in pain modulates brain activity in regions associated with physical pain and reward - Fox, Glenn R.; Sobhani, Mona; Aziz-zadeh, Lisa (Frontiers in Psychology, 2013)
How does witnessing a hateful person in pain compare to witnessing a likable person in pain? The current study compared the brain bases for how we perceive likable people in pain with those of viewing hateful people in pain. While social bonds are built through sharing the plight and pain of others in the name of empathy, viewing a hateful person in pain also has many potential ramifications. In this functional Magnetic Resonance Imaging (fMRI) study, Caucasian Jewish male participants viewed videos of (1) disliked, hateful, anti-Semitic individuals, and (2) liked, non-hateful, tolerant individuals in pain. The results showed that, compared with viewing liked people, viewing hateful people in pain elicited increased responses in regions associated with observation of physical pain (the insular cortex, the anterior cingulate cortex, and the somatosensory cortex), reward processing (the striatum), and frontal regions associated with emotion regulation. Functional connectivity analyses revealed connections between seed regions in the left anterior cingulate cortex and right insular cortex with reward regions, the amygdala, and frontal regions associated with emotion regulation. These data indicate that regions of the brain active while viewing someone in pain may be more active in response to the danger or threat posed by witnessing the pain of a hateful individual more so than the desire to empathize with a likable person’s pain.